Evaluating User Response to In-Car Haptic Feedback Touchscreens Using the Lane Change Test. (19th July 2012) - Pitts, Matthew J.; Skrypchuk, Lee; Wellings, Tom; Attridge, Alex; Williams, Mark A.
Abstract : Touchscreen interfaces are widely used in modern technology, from mobile devices to in-car infotainment systems. However, touchscreens impose significant visual workload demands on the user which have safety implications for use in cars. Previous studies indicate that the application of haptic feedback can improve both performance of and affective response to user interfaces. This paper reports on and extends the findings of a 2009 study conducted to evaluate the effects of different combinations of touchscreen visual, audible, and haptic feedback on driving and task performance, affective response, and subjective workload; the initial findings of which were originally published in (M. J. Pitts et al., 2009). A total of 48 non-expert users completed the study. A dual-task approach was applied, using the Lane Change Test as the driving task and realistic automotive use case touchscreen tasks. Results indicated that, while feedback type had no effect on driving or task performance, preference was expressed for multimodal feedback over visual alone. Issues relating to workload and cross-modal interaction were also identified.